Analysis of the time invariant Kalman Filter implementation via General Chandrasekhar algorithm. (15th April 2008) - Assimakis, Nicholas; Kechriniotis, Aristides; Voliotis, Stamatis; Tassis, Fotis; , Maria Kousteri
An implementation of the time invariant Kalman Filter using the General Chandrasekhar Algorithm is presented and compared to the classical one. A method is proposed to a-priori decide which implementation is faster.